2022
DOI: 10.1111/phen.12385
|View full text |Cite
|
Sign up to set email alerts
|

Physiological evaluation of newly invasive jorō spiders (Trichonephila clavata) in the southeastern USA compared to their naturalized cousin, Trichonephila clavipes

Abstract: A newly-invasive spider from east Asia, Trichonephila clavata, or "jor o spider", is spreading in the southeastern United States. Little is known about the biology or physiology of this species in this new range. Interestingly, a closely-related species in the same genus, the "golden silk spider," Trichonephila clavipes, is already successfully established in this same region over the last 160 years. The golden silk spider, which is native to the tropics, has not expanded its range beyond the southeast, likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Woodland has tree, shrub, and herbaceous layers, which can provide multiple predations and activity choices for animals in the vertical space (Souza et al, 2013). For example, our study found that Trichonephila clavata , an orb‐weaver, prefers to weave webs in tall trees (Davis & Frick, 2022), was collected only in woodland. Fallow land and woodland suffer less intensified agricultural practices than orchard and cropland, which also contributes to explaining their high abundance or diversity (Agra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Woodland has tree, shrub, and herbaceous layers, which can provide multiple predations and activity choices for animals in the vertical space (Souza et al, 2013). For example, our study found that Trichonephila clavata , an orb‐weaver, prefers to weave webs in tall trees (Davis & Frick, 2022), was collected only in woodland. Fallow land and woodland suffer less intensified agricultural practices than orchard and cropland, which also contributes to explaining their high abundance or diversity (Agra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We have observed T. clavata feeding on prey in several different arthropod groups, including cockroaches, beetles, wasps, bees, butterflies, dragonflies, grasshoppers, and other spiders (David R. Coyle, John F. Deitsch, Michael I. Sitvarin, personal observations). The high metabolic rate and quick maturation time of T. clavata (Davis & Frick, 2022) suggests a substantial amount of prey is taken, and thus not available to native orb weavers. Detailed studies of interactions between T. clavata and native orb weavers and prey are needed to better understand community responses to this invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It endures the harsh Korean winter (up to approximately -18 °C) until hatching in the following spring, but lays eggs with in loose eggpads containing large amount of CM. Previously found only in Eurasia, this species was recently reported for the first time in the Americas (Hoebeke et al 2015 ) and has expanded its range from southern United States as far as Oklahoma (Davis and Frick 2022 ).…”
Section: Introductionmentioning
confidence: 89%